Burnout Among Rural School Psychologists - E. Scott Huebner; Thomas J. Huberty (Journal of Research in Rural Education, 1983)
This article discusses conditions in rural school settings which may create or exacerbate problems of burnout among rural school psychologists. Specifically, problems concerning role and function, professional support, visibility and preservice training are related to rural practice. Also, suggestions for coping with stress and burnout in rural settings are presented.